Research data - the effect of high-pressure torsion on irradiation hardening of Eurofer-97 - Song, K; Strangward-Pryce, G L; Hofmann, F (University of Oxford, 2023)
It contains the raw and processed data collected as a part of the study which resulted in the manuscript 'The Effect of high-pressure torsion on irradiation hardening of Eurofer-97'. The data was collected and processed at the University of Oxford. Matlab is required to view most of the data. Some files are in Microsoft Excel format and Igor format. Data processing and plotting scripts are all included. The scripts are all written in Matlab.